Glass bead sterilization determination of time at which sterilization is effected - Hernandez, Erwin P.; Inocentes, Elvira A.; Manuel, Loida (Adviser).
In this study, 2 fillers of the glass bead sterilizer were tested as to what time sterilization was effected to the root canal instruments. And as to which of the two, big beads or small beads, was best at sterilization of the root canal instruments. Test results indicate that the glass bead sterilizer containing small beads can sterilize root canal instruments if the instruments are to be immersed for 11 seconds and that a 13 second immersion time is needed for the glass bead sterilizer containing big beads. As to the effectiveness of sterilization of both fillers, they both can completely sterilize the root canal instruments but one has to dip the instrument longer in the big beads before complete sterilization may be effected.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus -- Sterilization